2020
DOI: 10.1111/ipd.12681
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure and properties of primary carious molars treated using the Hall Technique

Abstract: Background The Hall Technique (HT) is a method of restoring decayed primary teeth using stainless steel crowns (SSCs) without tooth preparation, caries removal, or local anaesthetic. Aim To investigate the ultrastructural, biomechanical, and chemical characteristics of teeth managed with the Hall Technique in comparison with conventional SSC (controls). Design Twelve HT‐treated primary molars and four controls were analysed. Teeth were dehydrated in ethanol, embedded in methylmethacrylate, mesio‐distally secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Further, there was a lower mean hardness in HT-treated teeth than in controls. 15 Similarly, another study conducted in India found that children are free of any signs and symptoms of mandibular joint dysfunction following this technique, and any changes in the occlusion are settled four weeks after employing the HT. 16 Likewise, findings from one systematic review and meta-analysis showed that randomized controlled trials and quasi-experimental studies favored the HT in comparison to other approaches.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Further, there was a lower mean hardness in HT-treated teeth than in controls. 15 Similarly, another study conducted in India found that children are free of any signs and symptoms of mandibular joint dysfunction following this technique, and any changes in the occlusion are settled four weeks after employing the HT. 16 Likewise, findings from one systematic review and meta-analysis showed that randomized controlled trials and quasi-experimental studies favored the HT in comparison to other approaches.…”
Section: Discussionmentioning
confidence: 89%
“…Pre- and post-treatment X-rays revealed little to no caries progression over time, and Ca and P values were higher than previously reported for carious lesions in primary molars, implying that remineralization may have occurred in caries in HT-treated teeth. 15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the bacteria cannot produce acids, the cariogenicity of biofilm becomes less (5). In addition, when primary molars were treated with Hall Technique, it has been observed that although the hardness and elastic modulus of tissue was low, the calcium and phosphorus values to support remineralization were higher than the amount in the carious tissue without treatment (24).…”
Section: Discussionmentioning
confidence: 99%
“…The Hall Technique embraces changing concepts of managing dental caries, moving from the concept requiring its complete surgical excision, even at the expense of cavity size and pulpal health, to better understanding that caries in dentine can be slowed, arrested, and possibly even reversed, within a meticulously sealed environment. Owing to its non-invasive design, acceptance by patients, and rate of restoration longevity, the Hall technique may be an improved treatment option to increase access to care, decrease rates of untreated caries and provide a restoration that will allow for natural tooth exfoliation (6 ). Thus, the present study aimed to determine the efficiency of Hall Technique versus Formecresol Pulpotomy Technique regarding postoperative pain.…”
Section: Introductionmentioning
confidence: 99%